2006
DOI: 10.1159/000092231
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Growth Rate and Length on Fluoride Detection in Human Nails

Abstract: This study aimed to determine the lag time between increased fluoride (F) intake and F detection in human nails, as well as the influence of nails growth rate and length on this. Ten 20- to 35-year-old volunteers received 1.8 mg F daily, for 30 days. Nail growth rate and length were determined for all fingernails and toenails. Nail samples were collected at the beginning of the study and every 2 weeks (15 collections in all) and F concentrations were determined. The growth rate was statistically higher in fing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 28 publications
5
36
0
5
Order By: Relevance
“…A recent study has shown that this is not the case [Olympio et al, 2007]. In the present study, the results of Olympio et al [2007] were confirmed using nail F concentrations as response variables, since nails have been used as biomarkers of chronic [Whitford et al, 1999;Levy et al, 2004] and subchronic [Whitford et al, 1999;Correa Rodrigues et al, 2004;Buzalaf et al, 2006] F intake. Our results confirm that dentifrice pH does not seem to influence bioavailability of F, since nail F concentrations with the 1,100 ppm F ELDs were nearly identical, whether the pH was 4.5 or 7.0.…”
Section: Discussionsupporting
confidence: 78%
“…A recent study has shown that this is not the case [Olympio et al, 2007]. In the present study, the results of Olympio et al [2007] were confirmed using nail F concentrations as response variables, since nails have been used as biomarkers of chronic [Whitford et al, 1999;Levy et al, 2004] and subchronic [Whitford et al, 1999;Correa Rodrigues et al, 2004;Buzalaf et al, 2006] F intake. Our results confirm that dentifrice pH does not seem to influence bioavailability of F, since nail F concentrations with the 1,100 ppm F ELDs were nearly identical, whether the pH was 4.5 or 7.0.…”
Section: Discussionsupporting
confidence: 78%
“…Especially for F, nail clippings could play a relevant role to monitor F exposure and estimate risk for fluorosis. There are reports suggesting the use of nails as a biomarker for F exposure in animals [Buzalaf et al, 2002 and humans [Schamschula et al, 1985;Machoy, 1989;Czarnowski and Krechniak, 1990;Schmidt and Leuschke, 1990;Spate et al, 1994;Whitford et al, 1999;Levy et al, 2004;Rodrigues et al, 2004;Buzalaf et al, 2006]. Both fingernails and toenails have been used for this purpose, but the literature is contradictory regarding the relationship between fingernail and toenail F concentrations [Machoy, 1989;Whitford et al, 1999;Levy et al, 2004;Rodrigues et al, 2004;Buzalaf et al, 2006].…”
mentioning
confidence: 99%
“…Mean ± SD and (95% confidence interval) of F dose (mg F/kg body weight/day) to which children were exposed in phase A (diet +dentifrice) and in phase B (diet), and F concentration in fingernails (µg F/g) formed during these respective phases α (n = 23). that some studies have found a relationship between F exposure and F concentrations in fingernails (8,10), but others not (10,12). It should be emphasized that in the present study, it was estimated the dose to which the children were exposed from the dentifrice considering the soluble F concentration found in the dentifrice and not the one reported by the manufacturer because the dentifrice used contained calcium and part of F was insoluble.…”
Section: Discussionmentioning
confidence: 97%
“…However, data available in the literature are conflicting about their use to estimate the effect of F intake during toothbrushing (8)(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation